2018
DOI: 10.1371/journal.pone.0199577
|View full text |Cite
|
Sign up to set email alerts
|

Does partial replacement of corn with glycerin in beef cattle diets affect in vitro ruminal fermentation, gas production kinetic, and enteric greenhouse gas emissions?

Abstract: Five in vitro experiments were conducted with the following objectives: 1) To evaluate the ruminal fermentation of three different single ingredients: corn, glycerin, and starch (Exp. 1 and 2); 2) To assess effects of partially replacing corn with glycerin in beef cattle diets on ruminal fermentation pattern (Exp. 3 and 4); and 3) To evaluate the effects of glycerin inclusion on the extension of ruminal DM digestibility of feeds with high (orchard hay) and low (corn) fiber content (Exp. 5). For Exp. 1 and 2, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This behavior is presented by Almeida et al (2015) with incubation of cocoa husks that observed that the gases from the degradation of the NFC reached asymptote in period near the 12 hours of incubation while the volume of the gases from the degradation of the FC continued increasing beyond the 120 hours. Similarly, Benedeti et al (2018) observed that the asymptote of the gases from the starch fermentation was reached until 12 hours while corn continued its production beyond 48 hours. continuation For the sugarcane and peach palm, the France model showed the highest asymptote, while for the other feedstuffs the Orskov and McDonald (1979) model, without lag time, had the highest asymptote.…”
Section: Resultsmentioning
confidence: 80%
“…This behavior is presented by Almeida et al (2015) with incubation of cocoa husks that observed that the gases from the degradation of the NFC reached asymptote in period near the 12 hours of incubation while the volume of the gases from the degradation of the FC continued increasing beyond the 120 hours. Similarly, Benedeti et al (2018) observed that the asymptote of the gases from the starch fermentation was reached until 12 hours while corn continued its production beyond 48 hours. continuation For the sugarcane and peach palm, the France model showed the highest asymptote, while for the other feedstuffs the Orskov and McDonald (1979) model, without lag time, had the highest asymptote.…”
Section: Resultsmentioning
confidence: 80%
“…For the inoculum preparation of each animal, approximately 200 g of solid rumen contents were weighed and added to approximately 1 litre ruminal fluid in a blender. The blender was purged with CO 2 gas and blended for 2 min (adapted from method 3 DAISYII Incubator, Ankom Technology and Benedeti et al ., 2018). The blended digesta was filtered through four layers of cheese cloth into a preheated (39°C) 2 litre flask (Holden, 1999; Benedeti et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The blender was purged with CO 2 gas and blended for 2 min (adapted from method 3 DAISYII Incubator, Ankom Technology and Benedeti et al ., 2018). The blended digesta was filtered through four layers of cheese cloth into a preheated (39°C) 2 litre flask (Holden, 1999; Benedeti et al ., 2018). The flask was continuously purged with CO 2 gas.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, approximately 200 g of rumen solid particles were also added to the containers. For the inoculum preparation, the rumen content was blended for 2 min, followed by filtering through four layers of cheesecloth (Holden, 1999; Benedeti et al ., 2018 a ). The buffer mineral solution was prepared following the equipment manual and the pH was adjusted to 6.8 when needed (Holden, 1999).…”
Section: Methodsmentioning
confidence: 99%